2018
DOI: 10.1038/s41388-018-0327-8
|View full text |Cite
|
Sign up to set email alerts
|

The p21-activated kinase 4-Slug transcription factor axis promotes epithelial−mesenchymal transition and worsens prognosis in prostate cancer

Abstract: Epithelial-mesenchymal transition (EMT) facilitates cancer invasion and metastasis and thus accelerates cancer progression. p21-activated kinase 4 (PAK4) is a critical regulator of prostate cancer (PC) progression. Here, we report that PAK4 activation promotes PC progression through the EMT regulator Slug. We find that phosphorylated PAK4 (pPAK4) levels, an index of PAK4 activation, were tightly associated with Gleason score (p < 0.001), a clinical indicator of PC progression, but not with prostate serum antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 50 publications
3
29
1
Order By: Relevance
“…A number of recent studies have reported on the progression of PCa and EMT in TGF-β1 regulating PCa cells (43)(44)(45)(46). However, in the present study, we found that the auto-regulatory axis miR-20b-5p/TGFBR2/E2F1, which is regulated by TGF-β1, is involved in PCa development and progression through regulating EMTrelated gene expression.…”
Section: Discussioncontrasting
confidence: 73%
“…A number of recent studies have reported on the progression of PCa and EMT in TGF-β1 regulating PCa cells (43)(44)(45)(46). However, in the present study, we found that the auto-regulatory axis miR-20b-5p/TGFBR2/E2F1, which is regulated by TGF-β1, is involved in PCa development and progression through regulating EMTrelated gene expression.…”
Section: Discussioncontrasting
confidence: 73%
“…However, the underlying mechanism of the Linc01234/miR-433-3p axis in OSCC remains unclear. p21-Activated kinase 4 (PAK4), a member of the PAK family, regulates a wide range of cellular functions, including cell adhesion, migration, proliferation, and survival [26,27]. Previous studies have reported that dysregulation of PAK4 expression contributes to the development and progression of various tumors [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…P21was an inhibitor of the cyclin-dependent kinase and could inhibit the activation of CDK1, CDK2, and CDK4. TK1 might interact with P21 by combining with the C-terminal domain of P21, and promote the proliferation of cancer cells (21). In addition, growth and differentiation factor 15 was considered to be the main downstream mediator of TK1 function, which induced the metastatic attributes of lung cancer cells (22).…”
Section: Discussionmentioning
confidence: 99%